2016
DOI: 10.4265/bio.21.173
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Photosynthetic Bacteria and Isolated Bacteria in Their Antifungal Activities against Root Rot Fungi

Abstract: Antifungal bacteria AB in root rot fungus RRF -contaminated sweet potato farms were isolated, and seven strains were initially chosen as antagonistic candidates. An antagonistic test by using the mycelial disk placement method revealed that one AB strain by itself could inhibit the RRF growth. This AB strain was identified as Bacillus polyfermenticus based on phylogeny of 16S ribosomal RNA genes. Two AB strains Bacillus aerophilus displayed high levels of antifungal activity when paired with photosynthetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It should be noted that the same amount of autoclaved R. palustris GJ‐22 did not present any significant effect regarding growth parameters and resistance to TMV (Su et al ., ). Finally, it was demonstrated that the inoculation of R. faecalis increased the antifungal activity of several strains belonging to the Bacillus genus against the root rot fungus Helicobasidium mompa using disk placement tests (We et al ., ).…”
Section: Evaluating Use Of Pnsb As Fertilizer Biostimulant and Bio‐fmentioning
confidence: 97%
“…It should be noted that the same amount of autoclaved R. palustris GJ‐22 did not present any significant effect regarding growth parameters and resistance to TMV (Su et al ., ). Finally, it was demonstrated that the inoculation of R. faecalis increased the antifungal activity of several strains belonging to the Bacillus genus against the root rot fungus Helicobasidium mompa using disk placement tests (We et al ., ).…”
Section: Evaluating Use Of Pnsb As Fertilizer Biostimulant and Bio‐fmentioning
confidence: 97%